THE ROLE OF ADVERTISEMENTSIN ENGLISH FOREIGN LANGUAGE (EFL) TEACHING - Farida Hanim; citra anggia putri (FIP Unimed, 2015)
ABSTRACT This paper aims at discussing the use of advertisements (ads) in English Foreign Language (EFL) teaching and focuses on some of the appealing uses of language, visual elements, and culture in advertising, and on how language teachers could exploit them in their classes. Advertisers have creative ways to use ads to attract people’s attention and to be memorable by exploiting the language code, paralanguage, illustration and culture value. The ways of advertisers to use the language, illustration, code, and culture could be considered by the language teachers in teaching. Language teachers appears to be very little exploitation of the fascinating uses of language and visual elements in advertising, and this paper attempts to present EFL practice by providing an overview of some of the interesting uses of language, culture, and visual elements in ads, and suggesting ways of exploiting them in classroom. Keywords: advertisements, language code, illustration, culture value.